Perceived Confidence and Quality: Perception of Employers Towards Fresh Graduates: a Study in Malaysia - Hanie Abu Samah, Irza; Abashah, Aidanazima; Ummi Naiemah, Saraih (International Journal of Engineering and Technology, 2018)
Graduates quality has become a major issue recently especially in today’s scenario. Graduates quality can be varying when it perceived by employers. Different sector of industry has different standard of quality. The interpretation of employers towards graduates counts the job placement of graduates. It is hard to standardized quality across industries. Several attributes show that competence relatedness and autonomy do influence the quality of graduates. A quantitative method was used in this study for data gathering. All items were using 10-point likert scale. The content validity of this questionnaire were reviewed by five human resource professionals, and Cronbach alpha for each item is more than 0.75 which is acceptable. Questionnaires were given to the human resource officers in the company through email. Convenient sampling was applied in this study for data collection. 50 questionnaires were distributed across manufacturing industry and services industry in Malaysia. Using Partial least square to analyze the data, this study found out that competence in communication is the same criteria which majority across industries are seeking upon graduates. Therefore, Industries that involved are manufacturing (34.38%) and services (65.63%).  Measurement model and structural model were assessed to see the relationship. It shows that perception on competence has most influenced towards quality (AVE=0.849, R2=0.734=Q2=0.443).  This study concludes that employers around the world are looking at similar attribute on graduate’s competence. This study also warrants a future research, whereby researcher could get more sample size and by doing sample which involves employers, graduates and educators.